An Overview of Public Speaking Anxiety among International Students - Mudita, Chantika; Nurfarhanah, Nurfarhanah (Universitas Negeri Padang, 2025)
Public speaking is a crucial communication skill in various areas of life, including social, academic, and professional settings. This is especially true for international students, who are required to speak English. However, many students experience public speaking anxiety. Therefore, this study aims to describe the level of anxiety in public speaking among students of Guidance and Counseling (BK) International Class at Padang State University. The study uses a descriptive quantitative approach with total sampling of 59 students from the 2023 and 2024 cohorts. Data were collected through a four-point Likert scale questionnaire measuring four aspects: mood, cognitive, somatic, and motor. The results of the study indicate that the majority of students exhibit high levels of public speaking anxiety, with mood and cognitive aspects dominating. Meanwhile, somatic and motor aspects are relatively low. These findings underscore the need for counseling interventions to help students manage emotional stress and negative thoughts, thereby enabling their public speaking skills to develop optimally.